On Teaching Kim’s Convenience: Asian American Studies, Asian Canadian Studies, and the Politics of Race in Asian Canadian Theatre and Performance Studies - Daniher, Colleen Kim (Theatre Research in Canada / Recherches théâtrales au Canada, 2018)
This article offers a critical overview and rationale for why and to what ends Daniher put a comparative Asian North American method into practice in her classroom on Asian American Theatre and Performance Studies at Brown University in Spring 2016. In particular, Daniher focuses on pairing Ins Choi’s play-text Kim’s Convenience (2011) alongside a viewing of the made-for-PBS broadcast of Anna Deavere Smith’s Twilight: Los Angeles, 1992 (2001) in order to broach the topic of anti-Black racism in both Canada and the US in the Black Lives Matter moment . Although Daniher describes here a course and learning experience from within a US-American institutional setting, she directs the following emergent queries to the field of Canadian Theatre and Performance Studies in light of its recent inauguration of the new “sub-field” of Asian Canadian Theatre and Performance Studies: How should we frame Asian Canadian theatre and performance in the classroom? For what purpose and under what curricular conditions do we teach racialized “minority” repertoires of theatre and performance in Canada? Drawing on overlapping genealogies of Asian American and Asian Canadian Studies, Daniher contends that a more rigorous engagement with existing theories, methods, and critical analyses of racial power is urgently needed if Asian Canadian Theatre Studies hopes to coincide with the larger political-ethical stakes of “Asian Canadian studies projects” writ-large.